(untitled) (Journal of the College of Education for Women, 2019)
The current research aims at:Students know the level of the fourth phase of the Arabic languagedepartments in colleges of education in the discovery of the basic error ofgrammar by answering the following questions: 1. What level of students in the fourth stage of the Arabic languagedepartments in colleges of education in the discovery of the basic grammarerror?2. Is there a statistically significant difference between male and femalestudents in the discovery of the wrong grammar?3. What proposals to address the weakness of students in the grammar errordetection from the viewpoint of the teaching staff and Altdriciat?Determined by the current search by:1. Students in the fourth stage of the Arabic language departments in collegesof education infrastructure.2. Faculty and Altdriciat as a substance.3. AD 2010-2011 academic year.In the light of the findings of current research researcher concluded thefollowing:1 - a weakness in the level of students in the fourth stage of the Arabiclanguage departments in the faculties of basic education in the subject as, inparticular the (expressed) by about draws attention, and then, this weaknessthreatens the attainment of language and grammar for generations to comewho receive Arab and sciences at the hands of these students; because theywill graduate and become university teachers in the future.2 - about a lack of exercise in grammar, exercises in the area of set textsabout teaching in a special way.3 - the inability of students to discover the grammar error in the text.4 - not to link the material grammatical rules of other branches of the Arabiclanguage.5 - weak capacity of students to analyze the Arabic sentence in accordancewith rules and a specific scientific basis.6 - The teaching stresses in the education as to save the rule and Astzaarha,and this is seen as on the grounds that too and not a means to learn the Arabiclanguage and literature through the maintenance of tongue and pen, and thatthe expression can not be achieved by studying the theory but also throughongoing training.7 - The teaching of grammar is not through the understanding andcomprehension, but conservation-based automation, which is the methodused in teaching as evidence that the transfer of students to higher stages oflearning are often not accompanied by progress in their level.